Cervical range of motion in school age rugby union players: A cross sectional study. (July 2019) - Morgan, Richard; Wright, Sheila Leddington; Noon, Mark; Robertson, Paul; Price, Mike
Abstract: Objectives: Provide normative values for cervical range of motion and describe trends in school age rugby union players. Design: Cross-sectional study. Setting: National 3 level club. Participants: 59 school age rugby union players across under 8 (n = 8), under 9 (n = 9), under 10 (n = 15), under 13 (n = 13) and under 15 (n = 15) categories. Main outcome measures: Cervical range of motion using a cervical range of motion device (CROM) to determine values for active range of motion. Results: This study established mean ranges of motion for each age group. Pooled mean ranges with standard deviations for each direction were, flexion 66° (±11), extension 73° (±17), left rotation 69° (±9), right rotation 74° (±10), left lateral flexion 53° (±10) and right lateral flexion 49° (±12). No statistically significant differences were observed between the age groups, however, downward trends in lateral flexion were observed as age increased. School age rugby players had greater range of motion than senior playing counterparts. Conclusions: No statistically significant differences in ranges of motion were observed between the age groups of under 8 through to under 15. However, downward trends in some ranges of motion highlight the need for age specific monitoring for potential adaptations to continued playing and comparison to age matched non-rugby players. Inclusion of other risk factors such as head re-positioning sense should also be evaluated to help guide injury risk reduction strategies. Highlights: Normative ranges of motion for cervical movements in under 8, 9, 10, 13 and 15 age group rugby players. No significant differences in ranges between age groups. Trend for decreasing range of motion in lateral flexion as age increases.